2022
DOI: 10.1007/s13157-022-01533-x
|View full text |Cite
|
Sign up to set email alerts
|

The Economic Benefit of Coastal Blue Carbon Stocks in a Moroccan Lagoon Ecosystem: a Case Study at Moulay Bousselham Lagoon

Abstract: Land degradation is a problem that increasingly affects large areas of territories and affects various ecosystem services provided by coastal wetlands. These marine ecosystems provide valuable bene ts to the environment and to humans, including services such as coastal blue carbon sequestration (CBCS) the economic value of which is still poorly understood. This paper investigated land use/cover (LULC) changes in Moulay Bousselham lagoon (MBL) from 1971 to 2020 and their effects on CBCS variation. The transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Manzala Lake is a strategic environmental Lake of Egypt during last decade that was characterized by the extensive land cover change that affects negatively on the ecosystem services value. For Manzala lake, 12 million EGP was approved for developing the lake due to different problems (Egy-map 2020; Fahmy 2021), including the (Kacem et al 2022). Finally, the model that gives the relationship among a year of study and amount of carbon by hectare was calculated with high R 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Manzala Lake is a strategic environmental Lake of Egypt during last decade that was characterized by the extensive land cover change that affects negatively on the ecosystem services value. For Manzala lake, 12 million EGP was approved for developing the lake due to different problems (Egy-map 2020; Fahmy 2021), including the (Kacem et al 2022). Finally, the model that gives the relationship among a year of study and amount of carbon by hectare was calculated with high R 2 .…”
Section: Discussionmentioning
confidence: 99%
“…13. The expansion of cultivated land and urban areas had a slight in uence on C storage, as this change in LU/LC has mainly affected wet lawns and the edges of unused land (Kacem et al, 2022). Mekuria (2013) in his study reported that dense forest had higher total C stock followed by open forest, grassland, cultivated land, and bare land.…”
Section: Land Use Dynamic and Transition Probabilitiesmentioning
confidence: 97%
“…10. The expansion of cultivated land and urban areas had a slight influence on C storage, as this change in LU/LC has mainly affected wet lawns and the edges of unused land ( Kacem et al 2022). Mekuria (2013) in his study reported that dense forest had higher total C stock followed by open forest, grassland, cultivated land, and bare land.…”
Section: Land Use Dynamic and Transition Probabilitiesmentioning
confidence: 97%